ANALISIS STRATEGI MANAJEMEN HUBUNGAN BISNIS TERHADAP UMKM KOTA SURABAYA PASCA PANDEMI COVID 19 - Mahmud, Mahmud; Ashari , Muhammad Farhan; Mahendra , I.G.N. Andhika (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to examine the implementation of strategic management and business relationship management in the post-pandemic newnormal era. The COVID-19 pandemic has also shaken the global economy, including the Micro, Small and Medium Enterprises (MSMEs) sector in the city of Surabaya. To overcome these challenges, an effective business relationship management strategy is needed. This scientific article aims to investigate and analyze business relationship management strategies implemented by MSMEs in the city of Surabaya after the COVID-19 pandemic. This research uses a quantitative approach by collecting data through surveys and analyzing it using statistical methods.